K-MEDOIDS ALGORITHM ANALYSIS IN PERMANENT WORKER GROUPING OF INDONESIAN CONSTRUCTION COMPANIES - Tarigan, Sonia; Okprana, Harly; Saragih, Ilham Syahputra (Yayasan Kita Menulis, 2021)
The construction companies are both those who run the construction work, both construction administrators and construction consultants who need the manpower for their operations. There is no way to determine the existence of a policy of the workers who have a work agreement with the business owner for a period of time. The company's long-term rating of construction workers in Indonesia from 2010-2018 is based on the need to provide information and input to the local government center at the construction site in Indonesia. One of the grouping methods that can be used is k - Medoids. The advantage of this method is to overcome sensitive to outlier. This method in its horn is represented by objects close to the center and thus capable of sterilizing a more precise value. Analysis of the data grouping shows that two cluster data produced one in the low and 33 in high cluster with total cost of 2.7557.